Brittleness Evaluation of Shale Based on the Brazilian Splitting Test. (16th April 2018) - Hou, Bing; Zeng, Yijin; Fan, Meng; Li, Dandan
Abstract : Brittleness is an important mechanical parameter of shale reservoirs and has a significant effect on hydraulic fracturing. Traditional evaluation methods of shale brittleness are mainly based on complete stress-strain curves under compressive loading, which can barely describe the fracture characteristics of shale during hydraulic fracturing. This paper proposes to define the brittleness index based on the Brazilian splitting test and establishes a corresponding evaluation method, forming a tensile brittleness evaluation system for noncontinuous shale. The Brazilian splitting test and discrete element numerical simulation are carried out to study the crack distribution characteristics after tensile failure as well as the influence of anisotropy and scale effect on the brittleness of shale. The results show that the tensile brittleness index is more accurate and sensitive to condition changes than the compressive brittleness index. The experimental shale cores are from the Longmaxi formation, Silurian system, Sichuan basin.